A novel type of Co–Ti–Cr-base γ/γ′ superalloys with low mass density. (15th August 2017) - Zenk, Christopher H.; Povstugar, Ivan; Li, Rui; Rinaldi, Fernando; Neumeier, Steffen; Raabe, Dierk; Göken, Mathias
Abstract: A γ ′ strengthened Co–Ti–Cr superalloy is presented with a mass density ∼ 14 % below that of typical Co–Al–W-based alloys. The lattice misfit is sufficiently low to form coherent cuboidal γ ′ precipitates. Atom probe tomography shows that Cr partitions to the γ phase, but increases the γ ′ volume fraction compared to a binary Co-Ti alloy to more than 60 %. The solubility of Cr in the γ ′ phase is significantly higher than expected from previously published values. The γ ′ solvus temperature is above 1100 °C. The yield strength shows a distinct increase above 600 °C surpassing that of Co–9Al–8W (at.%) and conventional Co-base superalloys, even more so when it is normalized by the mass density. Graphical abstract: Image 1